6 - Ambivalence and Activism: Netizens, Social Transformation and African Virtual Publics - Ya’u, Yunusa Z. (Africa Development, 2021)
Despite the fact that Africa is the least connected continent on the internet, the use of information and communication technologies (ICTs) is becoming pervasive and deeply embedded in social and political relations. They are impacting on the way citizens live their lives and relate to both the state and other actors in the society. In this process, some citizens are becoming ‘netizens’. Cyber networking, which has been facilitated by access to ICTs, has given rise to a public sphere that is virtual. This paper explores some of the key issues relating to the development of ICTs in Africa and the social and political processes they have spawned in their wake. It is argued that while the virtual public is not unique to Africa, its manifestations, organisational modes, and concerns in Africa are informed by African conditions, both in terms of the specific issues addressed and the wider context of technological deficit that the continent faces.